(untitled) (Research, Society and Development, 2020)
Knowing the nutritional factors that limit pasture growth is essential for the production of forage in quantity and quality. The objective of the study was to evaluate the dry matter production of the aerial part and roots and the concentration of nutrients under nutrient omission conditions in fertilization, in the development of Urochloa brizantha cv. Marandu, during three growth cycles. The experiment was carried out in pots with dystrophic Ultisol at the College of Technology and Agricultural Science - Dracena Campus - FCAT / UNESP. The experimental design was randomized blocks, with eight treatments and five replications. The treatments were: 1- Complete fertilization; 2- Omission of fertilization; 3- N omission; 4- P omission; 5- K omission; 6- Mg omission; 7- S omission; 8- B omission. The results showed variation between the cuts in the dry matter production of the aerial part of Urochloa brizantha cv. Marandu, but in all, complete fertilization was among the highest yields. The nitrogen content was, among the studied elements, the most affected by the concentration effect in the forage. The levels of phosphorus, potassium and sulfur in the aerial part of Marandu showed levels considered adequate when nutrients were part of the treatment composition. The omission of nitrogen, potassium and sulfur were the nutrients that most affected the production of roots, while the initial levels of magnesium and boron in the soil were sufficient to meet the demand of Marandu.